Relationship between copper and immunity: The potential role of copper in tumor immunity - Cheng, Fu; Peng, Geng; Lu, Yan; Wang, Kang; Ju, Qinuo; Ju, Yongle; Ouyang, Manzhao (Frontiers in Oncology, 2022)
Copper is an essential trace element in an organism, and changes in copper levels in vivo often indicate a diseased state. Copper and immunity have been discussed since the last century, with copper deficiency significantly affecting the development and function of the immune system, such as increased host susceptibility to various pathogens, decreased number and impaired function of neutrophils, reduced antibacterial activity of macrophages, decreased proliferation of splenocytes, impaired B cell ability to produce antibodies and impaired function of cytotoxic T lymphocyte and helper T cells. In the past 20 years, some studies have shown that copper ions are related to the development of many tumours, including lung cancer, acute lymphoid leukaemia, multiple myeloma and other tumours, wherein copper ion levels were significantly elevated, and current studies reveal that copper ions are involved in the development, growth and metastasis of tumours through various pathways. Moreover, recent studies have shown that copper ions can regulate the expression of PD-L1, thus, attention should be paid to the important role of copper in tumour immunity. By exploring and studying copper ions and tumour immunity, new insights into tumour immunity could be generated and novel therapeutic approaches to improve the clinical prognosis of patients can be provided.